MP3 PLAYER APPLICATION PROGRAM USING MICROSOFT VISUAL BASIC 6.0 - Bambang Selva Ventri Agustianto; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2001)
The use of computers as a tool for solving human problems and human needs will be increasingly perceived entertainment. Technology contribute to many human lives. This is supported by the presence of other programming languages that support OOP (Object Oriented Programming). With the OOP techniques make it work programs become easier than before. Examples of programming languages that have supported this facility from Microsoft Visual Basic.In this writing, the author uses the Microsoft Visual Basic 6.0 to create an application program is intended for personal entertainment.